TREATMENT ADHERENCE IN PATIENTS WITH OSTEOPOROSIS IN DAILY CLINICAL PRACTICE - N. V. Toroptsova; O. A. Nikitinskaya; O. V. Dobrovolskaya (Научно-практическая ревматология, 2014)
Objective: to estimate the frequency of use of antiosteoporotic drugs in daily clinical practice and treatment adherence in patients. Subjects and methods. Questionnaires were used to interview two patient groups: 1) 198 women with osteoporosis (OP) with duration ≥3 years; 2) 186 women over 50 years of age who had sustained low-trauma fractures (LTF) at different sites and undergone assessments of therapy prescription and adherence 12 and 18 months after fracture. Results. In Group 1 patients with OP, 16, 24, and 38% of the women took antiosteoporotic treatment for >3, 2-3, and 6 months to 1 year, respectively; and 22% did not start pathogenetic therapy. Treatment adherence was significantly higher among those who were followed at the specialized OP Center. In Group 2, 56% of the patients had received therapy following LTF and 44% had not, which was due to the absence of primary care physicians' recommendations in half of the cases. 24% were treated after LTF within the first year and only 19% of the women were at 18 months. Treatment was recommended by the specialists of the OP Center in 89% of the cases and by primary care physicians in 11%. Within a year, repeated fracture occurred in 9% of the patients; among them none received pathogenetic treat- ment. A questionnaire survey of the patients indicated that they preferred to use drugs more rarely rather than every day. At the same time no advantages of any one route of drug administration were found. Conclusion. There is a low frequency of using pathogenetic treatment in patients with OP, particularly in those who are followed up in the district outpatient departments, which is due to both the absence of physicians' prescription of antiosteoporotic drugs and inadequate treatment adherence in patients. Both patient motivation to long-term treat- ment and OP education programs among primary care physicians are needed to improve the quality of medical care to osteoporotic patients.